Pemanfaatan Olahan Ikan Bandeng Menjadi Nugget: Solusi Inovatif untuk Penanganan Stunting dan Peningkatan Gizi Masyarakat Pesisir Tarakan - Theresia, Theresia; Indrawanto, Denny; Yulianto, Agus; Mumtaza Putri, Anne; Nur Farida Haryanto, Lailin; Hidayat, Rezaldi; Andriyanto, Andriyanto; Warol, Khoirul; Rohasad, Rohasad; Sauri, Salsabila; Giovani Siahaan, Fery; .Gandri Haryono, M; Firdaus, Muhammad (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
This community service program presents an integrated approach to address stunting through optimization of milkfish utilization as a high-nutrition food source. Despite Tarakan's coastal area having fisheries potential reaching 2.3 tons annually, local health department data reveals stunting prevalence of 24.3%. This paradoxical situation stems from low fish consumption among toddlers (only 32% of WHO recommendation), mainly due to children's preference for instant food and parents' limited knowledge in attractive fish processing methods. The program implements participatory learning methods through three main stages: interactive nutrition education, technical fish processing training, and micro-enterprise development mentoring. Ten mothers and children actively participated in all activities. Evaluation results show significant cognitive improvement with post-test scores reaching 82 compared to 41 in pre-test. On skills aspect, 88% participants could produce quality-standard fish nuggets. The establishment of two business groups with average weekly revenue of Rp1.2 million demonstrates the program's tangible economic impact